“Silencing the Voices of the Body”: Pathologization, Medicalization and Incarnated Emotions in Gynecological and Obstetric Violence Experiences in Chile (Palimpsesto, 2023)
The aim of this article is to investigate the social imaginaries that gynecology and obstetrics have built about women and their bodies, as well as the possible links with the violence that occurs in these health spaces, from the perspective of the users. Through focus goup in four cities in the country and a thematic analysis of the stories, I propose three central themes: experiences of body fragmentation; control operations (pathologization and medicalization); and incarnated emotions and body memory. I propose that gynecological and obstetric violence has a profound impact on the lives of those who suffer from it, confirmed in the activation of negative emotions and a body memory that lasts for a long time.
Keywords: Gynecological and obstetric violence; social imaginaries; pathologization/medicalization; incarnated emotions